The role of psychological capital in predicting academic achievement among undergraduate students of a Malaysian private university - Kuar, Lok-Sin; Ng, Lee-Peng; Choong, Yuen-Onn; Tan, Chun-Eng; Teoh, Sok-Yee (International Journal of Engineering and Technology, 2018)
Psychological resources may have an essential role in explaining students’ academic outcomes. The purpose of this study is to examine the influence of psychological capital on academic achievement among undergraduate students. In addition, the correlations of the individual component of psychological capital (hope, self-efficacy, resilience and optimism) and academic achievement were examined as well. The participants of this study are the undergraduate students from different faculties of a private university in Malaysia. The responses from 390 undergraduate students were used for data analysis. Results from Pearson correlation analysis show that hope, self-efficacy, resilience, and optimism were positively correlated with academic achievement. In hierarchical regression analysis, two demographic variables (gender and age) were controlled. The results revealed that psychological capital has a positive influence on undergraduate students’ academic achievement. As such, appropriate training interventions that can improve psychological capital among students should be designed.